Our History Clips: Collaborating for the Common Good - Beatrice N Bailey EDD; Nora McMillan (Middle Grades Review, 2017)
This case study reveals how middle school social studies teachers within a professional development program are encouraging their students to use multiple disciplinary literacies to create Our History Clips as they also work toward developing a classroom community of engaged student citizens.
Keywords: Disciplinary Literacies; Social Studies; Inquiry; Multimedia Exchange